Study on shear behavior of riveted lap joints of aircraft fuselage with different hole diameters and squeeze forces. (September 2021) - Li, Ming; Tian, Wei; Hu, Junshan; Wang, Changrui; Liao, Wenhe
Graphical abstract: Highlights: Material flow characteristics and interference distribution in the riveting process. The pop-up phenomenon of rivet manufactured head and driven rivet head in the shearing process. Brittle fracture and plastic fracture transition mechanism of rivet shank in the shearing process. Shear fracture stage division and shear failure mechanism. Abstract: Riveting is the most important method to connect metal sheets and is widely used in the joining of aircraft components. In the present research, the effect of different hole diameters and squeeze forces on the shear behavior of riveted lap joints is investigated. The variation of shear load with hole diameter under different squeeze forces was obtained by shear tests. Besides, the fracture mode and microstructure of the rivet shank were characterized by SEM, and the formation process of brittleness and plastic fracture was discussed. A 2D axisymmetric finite element model was established with the help of ABAQUS commercial finite element software and the validity of the finite element models was verified by experiments. To investigate the influence of interference distribution on the mechanical behavior of riveted lap joints, the interference distribution and material flow characteristics during the riveting process were analyzed in detail by the finite element methods. The results showed that all the specimens presented a mixed fracture mode of brittleness and plasticity at rivet shank. The area of the brittle fracture region was much smaller than the plastic fracture region. Also, the shear load was enhanced when the hole diameter increased from 4.82 mm to 5.10 mm. The maximum shear load increased by 17.77% and 17.24% under 15 kN and 23 kN squeeze forces respectively. In addition, compared with the squeeze force, increasing the hole diameter could effectively raise the shear load of the riveted lap joints.